Interdisciplinary actions in domiciliary health care - Elaine Alegre Bueno; Rodrigo de Souza Balk; Odete Messa Torres (Universidade de Santa Cruz do Sul, 2012)
KEYWORDS Domiciliary Health Care, Multidisciplinarity